Rare case of heterotopic pregnancy: a case report - Khanam, Rosy; Choudhury, Shabir A. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Heterotopic pregnancy refers to condition where two pregnancies are present simultaneously at different implantation sites mostly manifested as intrauterine and ectopic pregnancies. First heterotopic pregnancy after in vitro fertilization was reported in 1972. Mostly it is a sporadic condition. The most common ectopic site is the fallopian tube, both in spontaneous and assisted reproductive technology (ART) heterotopic pregnancies. Almost 60-70% of heterotopic cases result in live childbirth with outcomes similar to that of singleton pregnancies. Spontaneous heterotopic pregnancy is a rare and potentially dangerous condition in which intrauterine (IU) and extrauterine pregnancies occur at the same time. It can be a life-threatening condition and can be missed, with the diagnosis being overlooked. A high suspicion is needed in women with risk factors for an ectopic pregnancy and in low-risk women with an intrauterine gestation who have free fluid with or without an adnexal mass or in those presenting acute abdominal pain and shock. The ectopic component is usually treated surgically and the intrauterine one is expected to continue normally.